The Use of a Method of Du Pont to Assess Rentabilitas PT Unilever Indonesia Tbk a Period of the Year 2020 - 2021 - Evi Kurniasari; Wahyudiono (Jurnal Ekonomi, 2023)
The du pont method is the approach that will be used in the process of analyzing financial statements. Activity ratio analysis for profit on sales margin is a key component of the du pont method, which is used to calculate the company's profit. The purpose of this study is to assess the level of rentability of PT Unilver Indonesia Tbk in the period 2020 – 2021. This research uses a descriptive approach with quantitative data types. The results of the study using du pont analysis showed that the return on equity decreased which was influenced by the return on assets and equity multiplier, but the decrease in return on equity of -8.16 was more dominantly influenced by the return on assets showing a decrease of -15.98%. The decrease in return on assets was influenced by asset turnover and net profit margin which decreased by -3.80% and -12.65%, respectively, indicating that the company was not optimal in managing its assets to generate sales and the company had not been optimal in reducing expenses to achieve optimal profits.